2015
DOI: 10.1002/jobm.201400940
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus radicibacter sp. nov., a new bacterium isolated from root nodule of Oxytropis ochrocephala Bunge

Abstract: A Gram-positive, facultative anaerobic, rod-shaped, and endospore-forming strain, designated 53-2(T) was isolated from the root nodule of Oxytropis ochrocephala Bunge growing on Qilian mountain, China. The strain can grow at pH 7.0-8.0, 10-50 °C and tolerate up to 11% NaCl. Optimal growth occurred at pH 7.2 and 37 °C. The result of BLASTn search based on 16S rRNA gene sequence revealed that strain 53-2(T) , being closest related to Bacillus acidicola 105-2(T) , possessed remote similarity (less than 95.64%) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…The colony morphology was similar to those reported in Suganthi et al (2013). As the procedure was performed in aerobic conditions, the characteristics of rod-shaped, spore-producing, Gram-positive, and motile bacteria confirmed that the isolates were part of the Bacillus genus (Wei et al 2015).…”
Section: Discussionsupporting
confidence: 76%
“…The colony morphology was similar to those reported in Suganthi et al (2013). As the procedure was performed in aerobic conditions, the characteristics of rod-shaped, spore-producing, Gram-positive, and motile bacteria confirmed that the isolates were part of the Bacillus genus (Wei et al 2015).…”
Section: Discussionsupporting
confidence: 76%